G43(P) A retrospective study on the impact of contaminated blood cultures. (7th April 2014) - Flanagan, M; Nabialek, T; Nicholson, A; Okafor, I; McNamara, R
Abstract : Introduction: Blood cultures (BCs) are pivotal in the appropriate management of bacteremic infections in children. Bacteremia has a significant risk of morbidity and mortality and requires prompt hospital admission and treatment with intravenous antibiotics. There is thus a need to ensure that BC results are reliable and accurate. In order to minimise patient discomfort BCs are frequently obtained at the time of intravenous cannulation in the paediatric population, including patients with a low level of suspicion of sepsis. If aseptic techniques are not utilised in obtaining BCs, it is possible to contaminate BC samples with skin flora. Blood must be cultured for five days to rule out bacteremia, thus patients are often discharged home (if clinically well) before the final results are available. Aim: The aim of this study was to retrospectively determine the management and outcomes of patients who were called to return to hospital because of positive BCs. Methods: The Emergency Department (ED) admission log book was retrospectively studied over a 6 month period (January–July 2013) to identify patients who were called back from home because of positive BCs. All patient notes were then reviewed to obtain demographic, clinical and laboratory data. Results: 1066 BCs, equating to 983 children, were obtained in ED during the study time-frame. Eleven patients were phoned to return to ED because of positive BCs. Age ranged from 12 days to 7 yrs with 64% ≤2years. On initial presentation, two patients were pyrexial in ED, one had significantly raised leukocyte count (>15×10 9 /l) and four had a high CRP (>10 mg/l). Four children were prescribed oral antibiotics and one was admitted and subsequently discharged with suspected pertussis. The median time for BC growth was 19.9 h (range 13–54.7 h). When called back to the ED 10 patients were admitted, 54% received IV antibiotics and 36% were observed. All 11 BC results were subsequently deemed contaminants. Conclusions: This study highlighted the impact of BC contamination on both patient care and hospital services. In order to standardise optimal patient care the following should be addressed 1) criteria for taking blood cultures 2) guidelines for correct aseptic BC sampling and 3) protocol for following up positive BC results.